Service Quality in Indian Higher Education: A Comparative Study of Selected State Owned and Private Universities - Bhardwaj, Siddharatha S. (Indian Journal of Marketing, 2015)
Purpose: Imparting higher education in India, not so long back, was largely the prerogative of the state as the payment capacity of the masses prevented too many private players to venture into the education sector. Of late, however, the education sector has become one of the most sought-after businesses for both novice entrepreneurs as well as established players of corporate India. These are pouring money into the said sector to fetch reasonable return on their investment. The traditionally reliable state players too have started making efforts to add on to their image of reliable education providers. Already, it has become a debatable issue as to whether the private universities would be able to match the state owned universities on the reliability front and how will these counter the extremely low fees being charged by them. State universities, on the other hand, also have a task cut out for them as to how these will counter the excessive promotion being done by private entrants and deal with the tangibles created by the private players. The best way under the prevailing circumstances is to impart quality in educational services. The present study essentially aimed at assessing service quality as perceived by the students of selected state owned and private universities in the state of Haryana. Â  Research Type: Empirical ; Model Used : Self - Designed Findings: Both the sample state as well as the private university of Haryana had not yet come up to the expectations of the students on various service quality dimensions. Comparatively speaking, the relative position of the state university was better on the following fronts - service bonding, service value, service security, and service competence. The sample private university had a slight edge on service impressiveness and service promptness fronts. Practical Implications: The Indian education service providers should start viewing service quality from the viewpoint of the students and start bringing in necessary changes in their existing endeavours on the said front. Research Limitations: The technicalities involved in understanding the concept of service quality might have acted as a handicap for the students in giving prompt and accurate answers to the questions at hand.